Nests, Eggs, and Nestlings of the Restinga Antwren Formicivora littoralis (Aves: Thamnophilidae) - FLAVIA G. CHAVES; MAURICIO B. VECCHI; THIAGO F.S. LAURINDO; MARIA ALICE S. ALVES (Anais da Academia Brasileira de Ciências, 2013)
We describe the nest, eggs, and nestlings of the Restinga Antwren (Formicivora littoralis), an endangered bird of Restinga ecosystem (sandy coastal plain vegetation) that is endemic to Rio de Janeiro state. Twelve nests were found at the edges of trails or natural gaps at Massambaba Restinga region, in different supporting plants and heights from the ground (X ± SD 1.27 ± 0.97 m, range 0.27 to 3.45 m). Nests were cup-shaped and were in horizontal forks attached to branches at three to five points with whitish, soft, and thin cotton-like vegetable fiber. The nests' cup shape and measurements were similar to congeneric species, but nest material was different. Eggs were white with brown spots concentrated on the large end or around the middle, giving the appearance of a rough brown ring. Their mean (± SD) minimum diameter was 13.1 ± 0.34 mm, with maximum diameter of 18.0 ± 0.38 mm, and mass of 1.7 ± 0.18 g (n = 8). We found two nestlings completely naked on their first day after hatching.